2015
DOI: 10.1111/jcpt.12280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coenzyme Q10 supplementation on metabolic profile in diabetes: a systematic review and meta-analysis

Abstract: CoQ10 supplementation has no beneficial effects on glycemic control, lipid profile or blood pressure in patients with diabetes. However, it may reduce triglycerides levels. Due to limited data availability, well-powered and well-designed randomized controlled trials are needed to clearly determine the effect of CoQ10 on metabolic profile in diabetes. Dosage effects should also be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 37 publications
(154 reference statements)
2
65
2
Order By: Relevance
“…CoQ10 administration may improve markers of insulin metabolism through modulation of insulin and adiponectin receptors . In addition, CoQ10 decreases oxidative stresses and participates in endothelial metabolism, which in turn may result in an increase in lipolysis of triglycerides . These mechanisms might suggest the importance of CoQ10 administration in subjects with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…CoQ10 administration may improve markers of insulin metabolism through modulation of insulin and adiponectin receptors . In addition, CoQ10 decreases oxidative stresses and participates in endothelial metabolism, which in turn may result in an increase in lipolysis of triglycerides . These mechanisms might suggest the importance of CoQ10 administration in subjects with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study by Mehmetoglu et al [25], there was no significant correlation between serum CoQ10 levels and insulin resistance among obese and control subjects. In a meta-analysis [6] of seven studies, CoQ10 supplementation had no beneficial effects on lipid profiles in patients with diabetes. In addition, 200 mg CoQ10 supplementation per day for 12 weeks among patients with T2DM led to significant differences in total and LDL cholesterol levels compared with the placebo [26].…”
Section: Discussionmentioning
confidence: 97%
“…CoQ10 is an enzyme cofactor produced by most of the human cells, and it is necessary for the process of energy production in mitochondria [6]. Few studies have showed that CoQ10 deficiency is associated with numerous disease processes including CHD, cancer and diabetes mellitus [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets from patients with hyperlipidemia possess a lower threshold for aggregation and activation, this may be caused by increased circulating oxidized LDL (ox‐LDL), and oxidative stress . We noticed differing conclusions on whether CoQ10 improves lipid profiles (i.e., lower LDL levels) . A few studies failed to observe that CoQ10 supplementation affects serum LDL levels in CVD patients .…”
Section: Discussionmentioning
confidence: 99%